Population and spatial distribution of urbanisation in Peninsular Malaysia 1957 - 2000 - Tarmiji Masron,; Usman Yaakob,; Norizawati Mohd Ayob,; Aimi Shamimi Mokhtar, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
For the past 90 years Malaysia has experienced rapid urban population growth. Beginning with towns which grew from colonial tin mining and trading and spices industries, urban growth had proceeded in tandem with population growth and economic modernisation. This article discusses the process of population growth and urbanisation in Peninsular Malaysia from 1911 to 2000 whereby urban population data from population and housing census were utilised to analyse the spatial distribution of towns in the region. Geographic Information System (GIS) was used to analyse the spatial distribution and growth centres of the cities involved. The period spanning 1957 and 2000 was chosen to look at this phenomenon. In 1957 the number of cities recorded was only 33; this had increased by 400 per cent to 140 in 2000. The analysis also found concentration tendencies of Peninsular Malaysia’s urbanisation as testified by the rise of urban growth centres in Peninsular Malaysia for the same period examined.